The Needs of Rebranding at Business English Study Program to Attract Students (Nusantara Science and Technology Proceedings, 2022)
Choosing the right education for their children is the most crucial factor that parents must do especially in Indonesia. The popular choice for study must be an S1 university degree while studying in vocational education probably becoming the least choice despite the raising popularity of vocational education recently. One of the private vocational education institutions in East Java is Politeknik Ubaya. It has several study programs and one of the study programs is the Business English study program. Although it has been established for about twenty years the study program also struggles to attract more students. Therefore, in the middle of 2022, they decided to do a rebranding and change the curriculum becoming an English for Business and PR study program. The purpose of this study is to find the need for the rebranding of the Business English study program as well as the impact, whether the rebranding attracts more students or not. The research method used for this research is quantitative research by using questionnaires and non-formal interviews as a tool. The target respondents were the new students or semester one students of the study program. The writer has conducted preliminary observation for this review, and so far the study program attract more students to register, but the further in-depth study is needed to reveal the issue. This research will be beneficial for vocational education, especially to prove that rebranding can be an important factor to attract students. The suggestion for further research is emotional branding on vocational education to attract students.